Prebiotic Effects of Insoluble Konjac Glucomannan Derived from Edible “Konnyaku” on Weight Control - Chikako Shimokawa; Wakana Mizutani; Haruhisa Motegi; Naomi Gokan; Junichi Tomita; Hajime Hisaeda (Microorganisms)
Obesity is a major global health issue, and novel dietary approaches are needed for prevention and management. This study investigates the effect of insoluble konjac glucomannan (iKGM) derived from edible konnyaku, a traditional Japanese food, on weight gain suppression in mice. Mice treated with iKGM showed increased fecal volume, reduced food intake, and suppressed weight gain (Day 21; p < 0.01). This weight-suppression effect was prebiotic rather than physical properties of iKGM, as antibiotic treatment abolished the weight-suppressing effect despite increased fecal volume. iKGM treatment altered the gut microbiota, notably increasing Akkermansia muciniphila (Day 21; p < 0.01), a bacterium associated with weight loss, along with elevated levels of short-chain fatty acids (SCFAs) such as butyrate and propionate (Day 21; p < 0.01). Furthermore, iKGM-induced weight suppression was linked to elevated leptin levels (Day 21; p < 0.01), an appetite suppressant induced by SCFAs. These results suggest that iKGM modulates gut microbiota, increases A. muciniphila, induces leptin production, and reduces food intake, inhibiting weight gain. This study indicates that iKGM may represent a promising approach for obesity prevention through gut microbiota modulation. Future research should investigate the mechanisms of iKGM’s effects on microbiota and explore its long-term safety and efficacy in clinical trials.